Explaining Dynamic Marketing Capabilities Driven by Climate Change: An Exploratory Investigation of B2B Firms - Maryam Asgharinajib; Davood Feiz; Morteza Maleki Min Bash Razgah; Azim Zarei (‫مدیریت بازرگانی)
Objective Projections on the severity of climate change-related disruptions and displacements are becoming increasingly alarming over time (DiBella, 2020). Since climate change-related hazards have large impacts on a vast range of businesses, from individual traders to multinational companies (Canevari-Luzardo, 2020; Goldstein et al., 2019; Neise et al., 2018; Schneider, 2014; Surminski, 2013; Surminski et al., 2018), direct and indirect losses (e.g., damage to personnel, assets, and stocks) have been inflicted on businesses. Therefore, in environments where climate change has led to environmental uncertainty, it seems necessary for organizations to create new marketing strategies and capabilities to address this issue. However, considering the consequences of climate change, no research has yet identified the dynamic marketing capabilities based on climate change. On the other hand, past research has focused on B2B marketing capabilities in developed countries such as the United States (Mariadoss et al., 2011; Krush et al., 2015), the United Kingdom (Kaleka & Morgan, 2019; Yu et al., 2014), Australia (Merrilees et al., 2011; O'Cass & Weerawardena, 2010), and Germany (Helm et al., 2020; Wilden et al., 2019). As a result, the findings of these studies cannot be generalized to developing countries (Kamboj & Rahman, 2015; Mora Cortez & Johnston, 2018), where there are some of the most serious vulnerabilities to climate change (Odell et al., 2018). Additionally, since marketing is a contextual discipline (Sheth, 2011), the required marketing capabilities that drive firms' long-term performance can vary across countries and industries (Mora Cortez & Johnston, 2018). This is particularly relevant in Iran, which is one of the countries facing unprecedented problems related to climate change, including the drying up of lakes and rivers, dust storms, unprecedented temperatures, droughts, and floods (Vaghefi et al., 2019). Therefore, this research was conducted to fill these research gaps and to answer the question: "What is the conceptual framework of dynamic marketing capabilities driven by climate change?"